ANALYSIS OF THE INFLUENCE OF INTEREST RATE, EXCHANGE VALUE, WORLD GOLD PRICES, DOW JONES INDEX, AEX INDEX, DAX INDEX, AND SHANGHAI INDEX ON LQ45 INDEX IN INDONESIA STOCK EXCHANGE 2012 – 2018 - Andini Nurwulandari; Hasanudin Hasanudin; Ari Jatmiko Setiyo Budi (UNIVERSITAS INDRAPRASTA PGRI, 2020)
This research aims to find out the influence of interest rate, exchange rate, world gold price, Dow Jones Index, AEX Index, DAX Index, and Shanghai Index on the LQ45 Index at the Indonesia Stock Exchange from 2012 through 2018 using the ARCH/GARCH model as the method of analysis. The result of the test shows that the exchange rate had a significant negative influence, Dow Jones Index, AEX Index, and DAX Index had a significant positive influence on the LQ45 index, while the interest rate and world gold price had a non-significant negative influence and the Shanghai Index had a non-significant positive influence on the LQ45 index.